Transforming national folklore in digital space: A case study of Internet memes in modern Kazakhstan - Saltakova, Zhanat Toqtarkyzy; Oralbek, Almas; Mursalimova, Nassikhat; Kudaibergenova, Kunimzhan Tynyshyqbekovna; Kenbayeva, Ainur Zinelovna (Research Journal in Advanced Humanities, 2026)
This paper seeks to contribute to the semiotic analysis of hybrid forms in digital communication. It aims to explore the transformation of Kazakh folklore in digital spaces through a case study of 236 Internet memes featuring Kazakh cultural elements drawn from digital platforms such as Instagram, Tik Tok, and Telegram. The study has a mixed-methods design and combines thematic and semiotic analyses to look at how traditional oral narratives transform into multimodal, or creolized, digital phenomena. It allowed identifying the main thematic and semantic features characteristic of digital folklore. The thematic analysis identified the most frequently recurring themes in Internet memes and an essential dominance of spiritual values reflecting national Kazakh identity combining Nomadic traditionalism and modernity. The semantic analysis identified the main semantic features of Kazakh digital folklore depending on the number of semiotic components used, the nature of creolization tools, the composition of visual components, the significance of components, the degree of component correlation, and the method of component correlation. The findings of the research emphasize the shift from sacred extended narratives in traditional folklore to compressed creolized texts, which allows referring Kazakh digital folklore to glocal folklore combining global meme formats with local Kazakh specificity. The study fills gaps in digital folklore investigations in Central Asian contexts and offers insights into creolized semiotics for non-Western contexts.